L’institutionnalisation des Gender Studies en France : un processus à plusieurs niveaux - Farges, Patrick; François, Anne Isabelle (Romanica Silesiana)
Institutionalizing Gender Studies in France : A Multi-Faceted Process Processes of institutionalization and crossing are inseparable from ideological, political and societal issues: models and methods circulate, as texts travel without their contexts. Can this account for the differentiated reception of Gender and Queer Studies in France, particularly in comparison with other European countries? What specific impulses are thus realised in scientific areas and fields of research (literature, cultural history, arts…)? To what extent do the political and the institutional intertwine, in the academic as well as the educational context? Key words: Gender Studies, circulation, transfer, institutionalization.